Interaction of educational public policy and the internationalization of national universities in Barinas - Venezuela - González Valecillos, Yudith del Carmen (2023)
Public policies help to order the system of public organizations, including the educational system, which is why this research was developed, which analyzes the correlation between educational public policies and the internationalization of universities, in the state of Barinas, Venezuela.  This research assumed the empirical-analytical methodological approach, with a non-experimental, field and correlational design. The population was made up of the national (public) universities in the state of Barinas, and the intentional sample was 45 participants. Data collection was with a questionnaire-type survey using the Likert scale, validated by three experts with a reliability of .99% according to Cronbach's Alpha. Among the main findings, it stands out that the university is a subordinate actor and almost null, in issues of participation as a political actor in the process of educational public policy. Despite creating proposals for programs and projects in harmony with the territory hand in hand with the instances of popular participation. There is a waste of information generated in national universities and consequently limits communication and transparency in the management of Mppeu. Regarding internationalization, it can be said that it is a very incipient process, therefore, it is necessary to generate articulation strategies from the Mppeu together with the universities.